2007
DOI: 10.4081/ijas.2007.1s.397
|View full text |Cite
|
Sign up to set email alerts
|

Effect of packaging and aging time on shelf-life of beef meat

Abstract: The present study aimed to determinate beef meat shelf-life packaged in modified atmosphere (MAP). The experiment was carried out on young bulls Longissimus dorsii muscle and considered 2 thesis (meat portioned and conserved in MAP after 3 days “NA” and after 7 days “7A” of ageing), 2 types of packaging (with or without water absorbent pad) and 3 different conservation times (3, 7 or 11 days). The analysis regarded: water loss, colour, TBArs and protein ossidation. Liquid loss showed hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Previous studies have reported meat decolouration by HIU application at the same (22 W/cm 2 ) [25,37] or lower intensities (11 W/cm 2 ) in fresh meat from three different muscles [15]. Beef colour depends greatly on the chemical state of myoglobin, a sarcoplasm protein that may be easily oxide-reduced by the oxygen exposition resulting from quotidian physical or chemical processes in meat [38,39] (i.e., ageing [40], ultrasonication [10] or packaging [1,41]). HIU may detrimentally reduce meat colour when ultrasonication time is longer than 20 min, reducing redness and chroma and increasing the lightness [14,18].…”
Section: Physicochemical Traitsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have reported meat decolouration by HIU application at the same (22 W/cm 2 ) [25,37] or lower intensities (11 W/cm 2 ) in fresh meat from three different muscles [15]. Beef colour depends greatly on the chemical state of myoglobin, a sarcoplasm protein that may be easily oxide-reduced by the oxygen exposition resulting from quotidian physical or chemical processes in meat [38,39] (i.e., ageing [40], ultrasonication [10] or packaging [1,41]). HIU may detrimentally reduce meat colour when ultrasonication time is longer than 20 min, reducing redness and chroma and increasing the lightness [14,18].…”
Section: Physicochemical Traitsmentioning
confidence: 99%
“…In addition, the total colour change (∆E) of meat after SRD was not affected by the muscle; however, the ultrasonication showed a significant increase in the ∆E (see Figure 1B) with a consequent decolouration of the product after SRD. Together, the ageing [1], the high exposition to O 2 [48] and the ultrasonication might contribute to total decolouration of beef.…”
Section: Physicochemical Traitsmentioning
confidence: 99%
See 2 more Smart Citations